2017
DOI: 10.22478/ufpb.1981-1268.2017v11n1.33208
|View full text |Cite
|
Sign up to set email alerts
|

Temperatura e substrato na germinação de sementes e no crescimento inicial de plântulas de Sapindus saponaria (Sapindaceae)

Abstract: resumo -Sapindus saponaria é uma árvore da família Sapindaceae com madeira moderadamente pesada, dura, de baixa durabilidade natural, utilizada na construção civil e fabricação de caixotaria, além de possuir uso medicinal. Ocorre no Brasil desde o Pará até o Rio Grande do Sul, em florestas pluviais e semideciduais. O objetivo deste trabalho foi avaliar a germinação das sementes e crescimento de plântulas em diferentes temperaturas e substratos, com frutos e sementes coletados no Pantanal de Miranda, Mato Gross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 5 publications
(5 reference statements)
0
5
0
Order By: Relevance
“…The ability to germinate under extreme conditions allows the geographical and temporal distribution of a species, therefore optimizing its survival (Oliveira et al, 2017). So, the success of a species in heterogeneous environments relies on its plasticity (Lima et al, 2010).…”
Section: Effects Of the Environmental Stress On Germinationmentioning
confidence: 99%
“…The ability to germinate under extreme conditions allows the geographical and temporal distribution of a species, therefore optimizing its survival (Oliveira et al, 2017). So, the success of a species in heterogeneous environments relies on its plasticity (Lima et al, 2010).…”
Section: Effects Of the Environmental Stress On Germinationmentioning
confidence: 99%
“…However, the treatments with the lowest PCE values may have been characterized by low substrate moisture, making seed swelling difficult [17]. These results indicate that the most suitable substrate is the one that promotes a faster and more uniform emergence [23].…”
Section: Discussionmentioning
confidence: 99%
“…Normally the optimal temperature for cell division is approximately 30 ° C for most species and the results obtained for Eugenia stictopetala confirmed that this temperature was also the most adequate for its germination and initial growth. Oliveira and Pereira (2014) and Oliveira et al (2017), evaluating the best conditions for seed germination and initial formation of Guibourtia hymenaefolia (Moric.) J. Léonard seedlings, collected in areas of Serra de Bodoquena and Sapindus saponaria L., obtained in Pantanal, Mato Grosso also showed that the temperature of 30 °C was one of the most suitable for the evaluated species.…”
Section: Discussionmentioning
confidence: 99%